Understanding plant-pathogen interactions in Septoria tritici blotch infection of cereals - Petit-Houdenot, Y. (Burleigh Dodds Series in Agricultural Science, 2021)
Zymoseptoria is a major fungal pathogen of wheat, responsible for the Septoria Tritici Blotch (STB) disease. Recently, STB has been the subject of intensive molecular studies. Notably, massive transcriptomic analyses have helped to explore this particular bi-phasic (asymptomatic/necrotrophic) infection process. Cytological analyses have also improved our understanding of the asymptomatic phase. These advances suggest that Zymoseptoria behaves as a hemi-biotrophic fungus, acting like an endophyte during its asymptomatic phase. STB is still difficult to control. The emergence of fungicide-resistant isolates has reduced the efficacy of many fungicides requiring the development of novel fungicides and methods to counteract/reduce fungicide resistance. Likewise, because Stb-resistant wheat cultivars have all been successively defeated by virulent isolates, there is a need to identify new resistance genes in wheat, and to develop better disease resistance management methods (pyramiding, mixture/alternation) to sustainably control this pathogen.